An inclusive taxonomy of behavioral biases - David Peoń; Manel Antelo; Anxo Calvo-Silvosa (European Journal of Government and Economics (EJGE), 2017)
This paper overviews the theoretical and empirical research on behavioral biases and their influence in the literature. To provide a systematic exposition, we present a unified framework that takes the reader through an original taxonomy, based on the reviews of relevant authors in the field. In particular, we establish three broad categories that may be distinguished: heuristics and biases; choices, values and frames; and social factors. We then describe the main biases within each category, and revise the main theoretical and empirical developments, linking each bias with other biases and anomalies that are related to them, according to the literature.
Keywords: 330; Behavioral biases; decision-making; heuristics; framing; prospect theory; social contagion